2013
DOI: 10.1371/journal.pone.0058954
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterisation of Three O-methyltransferases Involved in the Biosynthesis of Phenolglycolipids in Mycobacterium tuberculosis

Abstract: Phenolic glycolipids are produced by a very limited number of slow-growing mycobacterial species, most of which are pathogen for humans. In Mycobacterium tuberculosis, the etiologic agent of tuberculosis, these molecules play a role in the pathogenicity by modulating the host immune response during infection. The major variant of phenolic glycolipids produced by M. tuberculosis, named PGL-tb, consists of a large lipid core terminated by a glycosylated aromatic nucleus. The carbohydrate part is composed of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Mutants with fitness costs included multi-gene loci associated with specific functional groups such as: the synthesis of lipids e.g. phthiocerol dimycolates (pDIMs) [ 44 ], phenolic glycolipids (PGLs) [ 45 ] and sulfolipids; cholesterol metabolism [ 46 - 48 ] and ESX systems [ 49 ] (Figure 2 c and Figure 3 ). Other functions associated with fitness are more scattered across the genome, but included PPE genes, the genes required for nitrate reduction and genes involved in the metabolism of methionine/cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…Mutants with fitness costs included multi-gene loci associated with specific functional groups such as: the synthesis of lipids e.g. phthiocerol dimycolates (pDIMs) [ 44 ], phenolic glycolipids (PGLs) [ 45 ] and sulfolipids; cholesterol metabolism [ 46 - 48 ] and ESX systems [ 49 ] (Figure 2 c and Figure 3 ). Other functions associated with fitness are more scattered across the genome, but included PPE genes, the genes required for nitrate reduction and genes involved in the metabolism of methionine/cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…Lipids from M. tuberculosis H37Rv (a 350-ml 7H9 culture without Tween 80 at an OD 600 of 0.5) treated with THL (50 g/ ml) or treated with the same volume of dimethyl sulfoxide (DMSO) as a control were extracted first with CHCl 3 /CH 3 OH (1:2 [vol/vol]) for 24 h at room temperature and then twice with CHCl 3 /CH 3 OH (2:1 [vol/vol]) for 2 days. Crude extracts were washed twice with distilled water and evaporated to dryness according to standard protocols as described previously (34).…”
Section: Methodsmentioning
confidence: 99%
“…I3-Ag85 inhibitory effect should therefore rely on the inhibition of additional targets, including potentially orthologous Ag85A or B proteins, given that the KO strain is devoid of Ag85C but shows the same MIC to the inhibitor as the WT strain. We therefore analyzed their lipid composition by high-pressure thin-layer chromatography (HPTLC) as previously described [10], comparing midlog-phase growing Mtb CDC1551 WT and KO cultures (with inoculum size 100 fold higher compared to drug susceptibility assays) , treated or untreated 24 h with 44 µg/ml I3-Ag85 [17]. As described by Warrier et al, we observed a slight decrease of TDM and an increase of DAT+TMM in the treated WT strain (Fig.…”
mentioning
confidence: 67%